2019
DOI: 10.3390/su12010329
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Impact of the Objective Characteristics and Subjective Perception of the Built Environment on Residents’ Physical Activities in Fuzhou, China

Abstract: Many researchers have confirmed a correlation between the built environment and physical activity. However, most studies are based on the objective characteristics of the built environment, and seldom involve the residents’ subjective perception. The purpose of this study is to explore the relationship between the subjective and objective characteristics of the built environment and physical activity at the community scale. Data consists of that collected from a social survey, Points of Interest (POI), the roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Four PNES measures were found to have a significant relationship with PA. First, the land use mix diversity was negatively associated with the PA. Respondents who believed that there was a high land use mix diversity tended to be C1, which was the opposite of the results in [57]. High land use mix diversity indicates that there is only a short distance to diverse land use in the respondent's location.…”
Section: Model 3 (Nusantara)mentioning
confidence: 62%
“…Four PNES measures were found to have a significant relationship with PA. First, the land use mix diversity was negatively associated with the PA. Respondents who believed that there was a high land use mix diversity tended to be C1, which was the opposite of the results in [57]. High land use mix diversity indicates that there is only a short distance to diverse land use in the respondent's location.…”
Section: Model 3 (Nusantara)mentioning
confidence: 62%
“…We found that accessibility to exercise facilities was signi cantly associated with moderate physical activity after adjusting for factors that might affect such activities; the easier the access, the higher the rate of physical activity. Other studies also found that physical activity is affected not only by the physical environment but also subjective perception [27][28][29][30][31] . We con rmed that the relevant social factors included sex, age, and income 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found that physical activity is affected not only by the physical environment but also subjective perception [27][28][29][30][31] . We con rmed that the relevant social factors included sex, age, and income 30,31 . Overall, men engaged in more exercise than women, but a subgroup analysis showed that the effect of accessibility to exercise facilities on moderate exercise was similar between the sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A United Nations Report focusing on Safe Cities and Safe Public Spaces establishes that when women and girls are not safe walking on city streets, it has a massive impact on their lives [20]. With regard to the environmental dimension of sustainability, higher levels of perceived security increase walking preferences and walking activity, this being the most sustainable form of travel [21,22]. With respect to the economic dimension, the costs of using private vehicles and the external costs associated with the use of motorized modes are reduced when walking is increased.…”
Section: Introductionmentioning
confidence: 99%